Ultras Futsal / Mohd Azrisyam Masri … [et al.] - Masri, Mohd Azrisyam; Abd Aziz, SyaAzli; Shahrun, Mohammad Azfar; Mat Salleh, Mas Azmira; Mohamad Za'aba, Nurdalilah (2018)
Our vision is to be referred as a world class indoor facility and preferred go-to facility for soccer lovers of all skill levels and to be amongst the top indoor soccer facility in Selangor.